2003
DOI: 10.4064/sm156-2-3
|View full text |Cite
|
Sign up to set email alerts
|

Topological reflexivity of the spaces of (α, β)-derivations on operator algebras

Abstract: Abstract. We prove that the spaces of (α, β)-derivations on certain operator algebras are topologically reflexive in the weak operator topology. Characterizations of automorphisms and (α, β)-derivations on reflexive algebras are also given. Introduction and preliminaries.The study of reflexive linear subspaces of the algebra B(X) of all bounded linear operators on the Banach space X represents a very active research area in operator theory (see [8] for a beautiful general view). The originators of this researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…He showed that if G is a locally compact group with an open subgroup of polynomial growth and X a Banach L 1 (G)bimodule, then Z n (L 1 (G), X), the space of bounded n-cocycles from A into X, is reflexive. More results related to these questions can be found in [6,8,12,13,14,15,16,18,19,20,29].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…He showed that if G is a locally compact group with an open subgroup of polynomial growth and X a Banach L 1 (G)bimodule, then Z n (L 1 (G), X), the space of bounded n-cocycles from A into X, is reflexive. More results related to these questions can be found in [6,8,12,13,14,15,16,18,19,20,29].…”
Section: Introductionmentioning
confidence: 98%
“…13), implies that|ϕ( f e 1 , h) − ϕ( f, e 1 h)| = |Φ( f e 1 ⊗ h − f ⊗ e 1 h)| |φ( f e n , h) − φ( f, e n h)| ≤ 8π 3all f, h ∈ A(T), where e n denotes the function in A(T) defined by e n (s) = e ins (s ∈ R, n ∈ Z).…”
mentioning
confidence: 99%